Pelatihan Penyusunan Bahan Ajar Bahasa Indonesia bagi Guru Smp/Mts di Surakarta - Huda, Miftakhul; Purwahida, Rahmah (WARTA, 2010)
This training has several goals, namely to open insights, and observers of Indonesian teachers about gender equality in everyday life, giving insight to analyze the value of inequality/ gender equality, and compile teaching materials Indonesian perspective of gender equality. Implementation of this training method is applied in two stages: the preparation stage and implementation stage. Preparation stage includes internal coordination (: preparatory concepts, preparation of materials) and the coordination of external (: contacting a speaker, contact the PDM Surakarta, Surakarta Dikspora contacted, and invited the school). Implementation stage is the stage of core training employed by interactive lectures, questions and answers, and tutorials. Training lasted for one day and 13 participants attended junior secondary school teachers. Based on analysis of implementation of teacher understand the preparation of teaching materials Indonesian gender perspective. This is evident from the responses of the material, examples, and instructional materials containing ilutrasi gender inequality.